Stepwise Evolution of Crease Patterns on Stimuli-Responsive Hydrogels for the Production of Long-Range Ordered Structures - Kim, Mina; Choi, Kwon Young; Kim, Ju Min; Shim, Tae Soup (Advanced Materials Interfaces, 2020)
The creases and wrinkles that form on soft matter have been comprehensively analyzed and engineered to utilize their topological advantages in various research fields. Although the principle for the formation of such structures is found to be the inhomogeneous distribution of mechanical stress, simultaneous and omnidirectional propagation of surface patterns makes it difficult to engineer these structures. A design strategy for the reversible formation of highly uniform crease patterns on hydrogel films is proposed by driving the stepwise evolution of creases. A hydrogel film with a smooth- and submicron-scale surface topology, so-called hill and valley structures, is prepared by engineering the reaction-diffusion-mediated photopolymerization and viscoelastic deformation of hydrogels. As the hydrogel film undergoes a morphological change in response to pH, creases are selectively nucleated from the hill and valley structures and propagate directionally, resulting in the formation of long-range ordered crease patterns. Different interactions are observed via the investigation of three colloidal systems, demonstrating the capacity to control colloidal particles with the highly uniform surface topology of hydrogels. Finally, the pattern-guided alignment and reproduction of yeast cells are demonstrated, providing an opportunity for producing an artificial environment for the guided growth and analysis of biomaterials.
Keywords: Artificial environments; Colloidal particle; Inhomogeneous distribution; Morphological changes; Ordered structures; Reaction diffusion; Reversible formation; Viscoelastic deformation; creases; guided cell growth; long-range ordered structures; reaction-diffusion processes; stimuli-responsive hydrogels